PELATIHAN PIJAT ENDORPHIN UNTUK MENURUNKAN INTENSITAS NYERI MENSTRUASI PADA SISWI SMPN 20 GRESIK - Safriana, Rizka Esty; Rachmawati, Aidha; Lestari, Dwi Linda; Aisyiyah, Finariqotul (Universitas Muhammadiyah Tapanuli Selatan, 2020)
SMPN 20 Gresik is one of the schools in the Gresik area, which has a total of 389 female students. Previously the students had never received education about reproductive health, especially about menstruation. The need for knowledge about adolescent reproductive health is still lacking, especially assistance for students in changing their reproductive organs. This community service activity aims to provide endorphin massage training to 126 class VIII students, which can be used as an alternative to reduce the intensity of menstrual pain in addition to taking pain medication. The result of this community service was that the students were very enthusiastic about participating in the activities carried out. Students increasingly understand the changes in reproductive organs that occur in adolescents, how to undergo menstruation with a healthy and comfortable, and can practice directly between friends in endorphin massage to reduce the intensity of menstrual pain.